Gerenciador web-móvel imobiliário utilizando Android e QR Code - Silva, Cedulio Cezar e (2012)
This work shows how the main theme the development of two applications using the methodology eXtreming Programming for the real estate, one focused on mobile devices using the Android operating system. The function of the mobile application is to read QR Codes and present data relating to real estate required for users to quickly and easily. The other application is directed to the web and aims to register the properties, users of the system, besides feeding the mobile application via XML files. To develop such applications were used the following technologies: Android, Google Maps API, library ZXing, QR Code, JavaEE, XML and MVC. The business rule used in this system shows promise in cities such as, for example, those with a high number of students, the residence time of the tenants in buildings is smaller, thus causing a significant movement in search of properties for rent.